A Strategy for Developing a Market for Nonperforming Loans in Italy - Jassaud, Nadege (IMF Working Papers; Working Paper, 2015)
Addressing the buildup of nonperforming loans (NPLs) in Italy since the global financial crisis will remain a challenge for some time and be important for supporting a sustained, robust economic recovery. The buildup reflects both the prolonged recession as well as structural factors that have held back NPL write-offs by banks. The paper discusses the impediments to NPL resolution in Italy and a strategy for fostering a market for restructuring distressed assets that could support corporate and financial restructuring.